Development of motor coordination during joint action in mid-childhood. (October 2017) - Satta, E.; Ferrari-Toniolo, S.; Visco-Comandini, F.; Caminiti, R.; Battaglia-Mayer, A.
Abstract: The ability to act jointly with others is a hallmark of primate evolution and is fundamental for human development. In recent years, the study of coordination strategies between individuals performing joint actions has received growing attention. However, when, in the course of post-natal development, this cognitive-motor function emerges is still unknown. Here, we studied dyads of peers aged 6–9 years, as well as adult subjects, while they performed a task where the same action, namely, exerting hand force on an isometric joystick to move a visual cursor from a central toward a peripheral target, was performed in a "solo" and in a social "cooperative" context. The results revealed that during joint action planning, an attempt to synchronize one's own action with that of a partner emerges at 7 years of age, together with a reduction in the duration and variability of the reaction times. A critical time is 8 years, when "solo" performance reaches a high level of accuracy. From this age, another coordination strategy, based on the online monitoring of the peer's behavior, seems to be implemented during the execution of joint action. The motor and cognitive development occurring during childhood are discussed as possible mechanisms mediating, respectively, the capability and the propensity to take into account the peer's behavior for implementing a common action plan. Graphical abstract: Highlights: We examined the ability of 6- to 9-year old children to act jointly in an isometric task. Synchronization between peers emerged during joint action planning at 7 years age. Coordination strategies during joint action performance emerged at 8 years age. Successful coordination was, at least in part, based on the online monitoring of the peer's behavior.